2015
DOI: 10.1021/acs.jproteome.5b00362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Glycosylation Site of Human PSA Prompted by Missense Mutation using LC–MS/MS

Abstract: Prostate specific antigen (PSA) is currently used as a diagnostic biomarker for prostate cancer. It is a glycoprotein possessing a single glycosylation site at N69. During our previous study of PSA N69 glycosylation, additional glycopeptides were observed in the PSA sample that were not previously reported and did not match glycopeptides of impure glycoproteins existed in the sample. This extra glycosylation site of PSA is associated with mutation in KLK3 genes. Among single nucleotide polymorphisms (SNPs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The identification and quantitation of a mutant glycosylation site (N102) of PSA were achieved for the first time, using C 18 ‐LC−MS analysis with different fragmentation methods (CID/HCD and ETD) . The amino acid sequences and associated glycoforms of three different PSA samples were successfully investigated, and it was demonstrated that HexNAc2Hex5 is the primary glycoform at N102, whereas HexNAc4Hex5Fuc1NeuAc1 or HexNAc4Hex5Fuc1NeuAc2 is the predominant form at N69 (Fig.…”
Section: New Glycomics and Glycoproteomics Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and quantitation of a mutant glycosylation site (N102) of PSA were achieved for the first time, using C 18 ‐LC−MS analysis with different fragmentation methods (CID/HCD and ETD) . The amino acid sequences and associated glycoforms of three different PSA samples were successfully investigated, and it was demonstrated that HexNAc2Hex5 is the primary glycoform at N102, whereas HexNAc4Hex5Fuc1NeuAc1 or HexNAc4Hex5Fuc1NeuAc2 is the predominant form at N69 (Fig.…”
Section: New Glycomics and Glycoproteomics Biomedical Applicationsmentioning
confidence: 99%
“…The fragments indicating N102 glycosylation and the carbamidomethylation of methionine are highlighted in yellow. Reprint with permission from .…”
Section: New Glycomics and Glycoproteomics Biomedical Applicationsmentioning
confidence: 99%
“…Glycomics changes associated with trumatic brain injury were also assessed using the above LC‐MS/MS analysis of permethylated glycans . Glycans derived from glioma stem cell xenografts , neuroblastoma and breast cancer cell lines, IgG , prostate‐specific antigen , and human milk, bovine milk, and goat milk were also analyzed using RPLC‐MS/MS of reduced and permethylated glycans.…”
Section: Rplc Separation Of Glycans Using Msmentioning
confidence: 99%
“…The challenge of confident assignment by database searching has necessitated simplification of the database by either reduction of the glycan [e.g., truncation of the glycan in a complex proteome (Steentoft et al, 2011; Zielinska et al)], or reduction of the proteome [e.g., glycoprotein immunoprecipitation (Song et al, 2015; Song et al, 2014)]. Methods to survey the intact glycoproteome from complex samples are assisted by advances in MS methods and database searching (Medzihradszky et al, 2015; Trinidad et al, 2013; Wu et al, 2014).…”
Section: Commentarymentioning
confidence: 99%